Historiographical Review of the Problem "Woman of the USSR in the Great Patriotic War – Hero or Victim?" - Saktaganova, Z.; Sagatova, A.; Nurligenova, Z. (Utopía y Praxis Latinoamericana, 2020)
The researchers often addressed various aspects of the Great Patriotic War, but the problem of "women and war" has rarely attracted the attention of researchers. Depending on the theoretic-methodological and conceptual approaches, the specifics of the sources involved, the range and depth of the problems raised among the whole set of available publications, the authors of the article highlighted three main types in historiography: Soviet, modern Kazakhstan and foreign (Russian and Western) historiography. The main trends that characterize each of these groups have been identified. It is concluded that in Soviet and Kazakhstan historiography many layers of problems were out of the research field: women never became objects of study.
Keywords: Great Patriotic War; women in war; historiography of the problem; war and violence